PDCA sebagai Upaya Peningkatan Target Perusahaan Plant B di PT X - Siswanto, Diana Porwanti; Aysia, Debora Anne Yang (Jurnal Titra, 2014)
Plant B is a plant that producing cigarette packaging industry, wants to apply continuous improvement through Quality Control Circle. Quality Control Circle is a program that involves a group of workers in a team to implement PDCA. Plant B has four Quality Control Circle projects which are project QCC NCR AMB, project QCC HL MBM ID, project QCC HL IB, and project QCC SP DSS 12.. The continuous improvement goal is based on Key Performance Indicator Target and Internal Target Company, which are determined by management. After improvement there is only one NCR blank print for project QCC NCR AMB. The waste precentage after improvement for project QCC HL MBM ID based on the last two jobs are 12.01% and 17.81%. The waste precentage after improvement for project QCC HL IB based on the last job is 15.29%. The waste precentage after improvement for project QCC SP DSS 12 based on the last two jobs are 4.6% and 3.26%.